How we approach genetics in the diagnosis and management of vascular anomalies. (7th September 2022) - Setty, Bhuvana A.; Wusik, Katie; Hammill, Adrienne M.
Abstract: Vascular anomalies are a heterogeneous group of disorders that are currently classified based on their clinical and histological characteristics. Over the past decade, there have been significant advances in molecular genetics that have led to identification of genetic alterations associated with vascular tumors, vascular malformations, and syndromes. Here, we describe known genetic alterations in vascular anomalies, discuss when and how to test, and examine how identification of causative genetic mutations provides for better management of these disorders through improved understanding of their pathogenesis and increasing use of targeted therapeutic agents in order to achieve better outcomes for our patients.